Sounds and Meanings Working Together: Word Learning as a Collaborative Effort. Issue 2 (September 2014) - Saffran, Jenny; Molnar, Monika; Sebastian‐Galles, Nuria
<x xml:space="preserve">Abstract</x> Over the past several decades, researchers have discovered a great deal of information about the processes underlying language acquisition. From as early as they can be studied, infants are sensitive to the nuances of native‐language sound structure. Similarly, infants are attuned to the visual and conceptual structure of their environments starting in the early postnatal period. Months later, they become adept at putting these two arenas of experience together, mapping sounds to meanings. How might learning sounds influence learning meanings, and vice versa? In this article, I describe several recent lines of research suggesting that knowledge concerning the sound structure of language facilitates subsequent mapping of sounds to meanings. I will also discuss recent findings suggesting that, from its beginnings, the lexicon incorporates relationships among the sounds and meanings of newly learned words.